ANALISIS POTENSI OBJEK WISATA DI KOTA JAMBI - ICA PUTRI MINANG SARI, UTARI ARDILLA; Yuliana, Yuliana; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The purpose of this research is to describe the cultural potential in the city of Jambi. This research consists of one indicator of potential tourist attraction that is: cultural potential. The type of this research is descriptive research with qualitative data. Informants in this study are: Head of Tourism of Jambi, Head of Program Development Tourism of Jambi, business cultural attractions in the city of Jambi, visitors to the cultural attractions in the city of Jambi and communities around the cultural attractions in the city of Jambi. The research found few potential of culture in Jambi, namely, archaeological sites or prehistoric form of: 1) Rumah Batu Olak Kemang, 2) Makam Habib Idrus Bin Hasan A-jufri (Pangeran Wiro Kusumo) and Makam Keramat Tambak Husein bin Ahmad Baragbah Jambi Kota Seberang, 3) Museum Perjuangan Rakyat Jambi, 4) Museum Siginjei, 5) Museum Gentala Arasy, 6) Al-Falah Mosque (Mosque of the Thousand Pillar). Traditional customs: 1) Adat pernikahan, 2) Rumah tradisional, 3) Makanan Khas Jambi (Tempoyak, Malbi, Gulai tepek, Padamaran, Nasi Keryak), Arts and Crafts: 1) Jambi Batik, 2) Woven and Wood Carving, 3 ) Kompangan (Hadra), 4) Tari Sekapur Sirih, 5) Tari Kompangan Bedana, 6) Tari Zapin Tekuluk, 7) Harmony Festival, 8) Haul.Keywords: Cultural Potential, Tourist Attraction.